Równania ruchu układów z silami uderzeniowymi - C. Cempel (Engineering Transactions, 1969)
This work is an attempt formulate the impact effect in a differential equation of motion of a system. By means of limiting transition the impact force was defined and the simple form of differential equation was obtained. This equation is a distributive one. Then the general manner of construction the equation of motion for impact system is shown. By means of Laplace transformation the solutions of these equations are obtained for uncomplicated cases.